2019
DOI: 10.35530/it.070.04.1551
|View full text |Cite
|
Sign up to set email alerts
|

An efficient ultrasonic and microwave assisted extraction of organic Henna dye for dyeing of synthetic polyester fabric for superior color strength properties

Abstract: Extracție eficientă cu ultrasunete și microunde a colorantului organic Henna pentru vopsirea materialelor textile sintetice din poliester cu proprietăți superioare de rezistență a culorii Tehnică de extracție eficientă din punct de vedere energetic și ecologică pentru extracția colorantului organic Henna a fost propusă pentru vopsirea materialelor textile sintetice din poliester, cu proprietăți de rezistență ridicată a culorii, pentru a satisface cererea mondială de procese și produse eficiente din punct de ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This result corresponds to the highest value of conversion efficiency recorded for red cabbage photosensitizer [34]. Extraction of dyes from Mangosteen peels by first milling and drying them for 3 -5 days before soaking in ethanol with stirring for 12 hours at room temperature, the absorption spectra of dye solutions were characterized by using UV-Vis spectrophotometer, anthocyanin of mangosteen peels was 400 -480 nm with power conversion efficiency of 0.042 % [31]. Kartini and Hatmanto extracted dyes from bark of tingi, tegeran and dried fruits of jalawe using aqueous and solvent extraction methods, they observed absorption peaks at 540 nm, 538 nm and 403 nm respectively [35].…”
Section: Fermentation Extractionmentioning
confidence: 81%
See 2 more Smart Citations
“…This result corresponds to the highest value of conversion efficiency recorded for red cabbage photosensitizer [34]. Extraction of dyes from Mangosteen peels by first milling and drying them for 3 -5 days before soaking in ethanol with stirring for 12 hours at room temperature, the absorption spectra of dye solutions were characterized by using UV-Vis spectrophotometer, anthocyanin of mangosteen peels was 400 -480 nm with power conversion efficiency of 0.042 % [31]. Kartini and Hatmanto extracted dyes from bark of tingi, tegeran and dried fruits of jalawe using aqueous and solvent extraction methods, they observed absorption peaks at 540 nm, 538 nm and 403 nm respectively [35].…”
Section: Fermentation Extractionmentioning
confidence: 81%
“…Microwave increases the rate of the processes so the extraction can be completed in a shorter time with better yield. Rabia, et al, extracted henna dye by ultrasonic and microwave assisted extraction method and observed that the method yielded more superior colour strength properties compared to other extraction techniques they had used [31].…”
Section: Components Of Dsscmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the reflectance value at maximum absorption, the color yield (K/S) was calculated with the Kubelka-Munk equation Eq. 1 [27] K/S = (1-Rλmax) 2 (1)…”
Section: Characterizationmentioning
confidence: 99%
“…[5][6][7][8] Several approaches have been studied to improve the sorption of natural dyes by textile fibres without the use of metal mordants. Application of plasma, 9,10 bio-mordants, 11,12 chitosan, 13 cationising agents, 14 ultrasound 15,16 and microwave 17,18 are among the most studied methods for elimination of metal mordants from natural dyeing processes. Silk sericin is another eco-friendly material which has the potential to improve the dyeability and functional properties of wool considerably.…”
Section: Introductionmentioning
confidence: 99%